2022
DOI: 10.3389/fmed.2022.940784
|View full text |Cite
|
Sign up to set email alerts
|

Altered Lung Microbiome and Metabolome Profile in Children With Pulmonary Arterial Hypertension Associated With Congenital Heart Disease

Abstract: BackgroundsPulmonary arterial hypertension (PAH) is characterized by progressive pulmonary vascular functional and structural changes, resulting in increased pulmonary vascular resistance and eventually right heart failure and death. Congenital Left-to-Right shunts (LTRS) is one type of congenital heart disease (CHD) and PAH associated with the congenital Left-to-Right shunt (PAH-LTRS) is a severe disease in children. However, changes in the lung microbiome and their potential impact on PAH-LTRS have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 73 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…Mounting evidence suggests that the gut-dwelling Lactobacillus and its components play a key role in modulating the immune system through stimulating immunological signaling between the gastrointestinal tract and distant organs (58). Consistently, Ma et al have also demonstrated that the increased abundance of Lactobacillus is associated with PAH compared with healthy volunteers and congenital left to right shunt heart diseases (59).…”
Section: Discussionmentioning
confidence: 91%
“…Mounting evidence suggests that the gut-dwelling Lactobacillus and its components play a key role in modulating the immune system through stimulating immunological signaling between the gastrointestinal tract and distant organs (58). Consistently, Ma et al have also demonstrated that the increased abundance of Lactobacillus is associated with PAH compared with healthy volunteers and congenital left to right shunt heart diseases (59).…”
Section: Discussionmentioning
confidence: 91%
“…The design of all studies was case-control (Table 1). Two articles were focused on pediatric and adolescent populations (15,16), while the rest of the studies were undertaken on adults (17)(18)(19)(20)(21)(22). In the majority of studies, females were more prevalent than men among PH cases (18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…Endotoxin level was increased among PH patients due to chronic thromboembolism (18), while, there was no signi cant difference between PH patients due to different etiologies compared to healthy controls in another study (21). Also, different metabolite levels were reported to be changed among PH patients such as short-chain fatty acid (SCFA) and bile acid (BA) (15,21). Interestingly, only one study reported alterations in trimethylamine N-oxide (TMAO) levels and there was no difference between PH and control samples, however, it was signi cantly increased among patients with higher REVEAL scores (21) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, three predictors (based on plasma concentrations of DBH, ANPEP, and ADIO) were detected in patients with congenital ventricular septal defect PH. Ma et al (95) performed 16 S rRNA sequencing and metabolomics analysis on bronchoalveolar lavage fluid of PAH associated with the congenital Left-to-Right shunts (LTRS), patients with LTRS but no PAH, and the healthy group. The integration of multi-omics showed that the pulmonary microbes and metabolites may be potentially effective biomarkers.…”
Section: Integrating Omics In Pah-chdmentioning
confidence: 99%